Photojournalism in nineteenth century Brazil - Marocco, Beatriz (Javnost (Ljubljana), 2007)
The essay focuses on the work of two German photographers, Augusto Stahl and Revert Henrique Klumb, whose work predates the journalistic genre of photojournalism in nineteenth century Brazil. The author proposes the use of a Foucaultian archaeology as a method of exploring and analysing the contributions of these photographers to the journalistic discourse, and to reporting in particular.
Keywords: Brazilija; časniki; časopisi; journalism; novinarstvo; novinarji; List of photographers; fotografi; dokumentarna fotografija; fotografski motivi